Price asymmetries in European airfares - Scotti, Davide; Volta, Nicola (Elsevier, 2018)
This research analyses airlines' pricing decisions in response to changes in the market conditions. We estimate the effects of jet fuel price changes on European airfares at airline/route level by discriminating on the grounds of supplied capacity and markets’ competitive structure. Our results show that airlines tend to adjust fares asymmetrically following a “rocket and feather” behaviour. The asymmetric pricing is marked in periods of decreasing capacity when the increases of fuel price are passed at a higher degree than fuel cost savings. In contrast, when capacity increases the asymmetry is lowered. Moreover, we show that highly competitive markets are characterized by a lower price asymmetry compared to low competition markets. Finally, our results show that airline price asymmetry reaches its maximum when capacity is reduced and competition is low.
Keywords: Airlines; Price asymmetry; Pass-through rate; Fuel cost